Advanced Principal Component Analysis of Various Risk Factors of Hepatitis B Prevalence in Nigeria - Adesina, Olumide Sunday (Tanzania Journal of Science, 2024)
Hepatitis B virus (HBV) is an infectious disease globally estimated to have caused between 500,000 to 1.2 million deaths annually. HBV prevalence is still high in Nigeria. Thus, this research aimed to identify factors germane to the widespread of HBV infection in an apparent clinical survey. The methods of analysis used were frequency, percentage and Principal component analysis (PCA). This was achieved through hospital record extracts of consultant hepatologists and the dimensionality reduction of the acquired data while retaining essential factors that are germane to the prevalence of HBV infection. The findings revealed that out of seventeen components evaluated in the study, the PCA retained 15 components of which Eigen-values are greater than 1.00. The symptoms retained in every component were fever, muscle pain, fatigue, loss of appetite, blood in vomit, jaundice, pale stool, nausea, blood in faeces, weight loss, malaise, abdominal pain, joint ache, swollen of lower extremities, confusion and yellow eye. The symptoms were listed in accordance with their level of relevance for diagnosing HBV in patients, and all the variables retained accounted for 94.278% variation in the prevalence of HBV infection, with the majority of the infected populace found among the adults (18 -64 years).